Love on the Margins: The American Indie Rom-com of the 2010s - Oria, Beatriz (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2018)
Ever since Brian Henderson famously diagnosed the death of romantic comedy in 1978 there have been numerous attempts to “kill” the genre. In view of its apparent lack of popularity in the 2010s, scholars and popular culture writers are proclaiming, once more, its demise. This article aims to question this view, arguing that the genre is alive and well, though living largely on the margins and finding alternative ways to re-imagine itself. It interrogates the term “independent” and uses genre theory to produce a non-taxonomical definition of the “indie rom-com” in the 2010s. With this purpose, this work outlines the basic conventions of these films and ends with a close analysis of a recent indie rom-com: Jim Strouse’s People, Places, Things (2015). The essay concludes that the relative mainstream dearth of the genre is masking a notable presence in other less visible sites. Contemporary romantic comedy is currently leading a “secret life” right before our eyes, independent cinema being rife with exciting examples of the genre. These films are finding new formulas that will eventually result in the reinvention of the genre at a larger scale, and not just in the independent sector. Keywords: romantic comedy; independent US cinema; indie rom-com; film genre; generic conventions; People, Places, Things